Relationship between the occurrence of cards, playing position and situational variables in starter and non-starter players in the Brazilian soccer first division championship - Gabriel Silveira Guedes da Maia; Paulo Vitor de Souza; Paulo Roberto Sandi; Guilherme Souza Pereira; Paulo Henrique Borges; Anderson Santiago Teixeira; Elisa Dell'Antonio; Juliano Fernandes da Silva (Termedia Publishing House, 2023)
Purpose To evaluate the moderating effect of the match starting status in the association of playing position and situational variables with the occurrence of punitive cards during Brazilian first-division soccer matches over three consecutive seasons. Methods The present study evaluated 1,140 matches in three seasons of the Brazilian first-division soccer championship (2018, 2019 and 2020). This is a descriptive correlational study with a case-control design. Results Over the three seasons, 5,490 cards were distributed. Match starting status moderated the association of the outcome with the playing position, current and final ranking position, season, match exposure time and minutes played. The starter's midfield players were more likely (OR: 1.244, 95% CI: 1.155 to 1.341) to receive a card and forward players were less likely (OR: 0.912, 95% CI: 0.830 to 1.003) to receive a card than the defenders. The starter's players were less likely to receive a card in the 2019 (OR: 0.889, 95% CI: 0.822 to 0.961) and 2020 (OR: 0.827, 95% CI: 0.764 to 0.896) seasons than in the 2018 season. Their (OR: 0.776, 95% CI: 0.532 to 1.140) and the non-starter's (OR: 0.491, 95% CI: 0.210 to 1.272) players were less likely to receive a card when the match ended with goal difference (GD) 2 goals between the two teams. The nonstarter's (OR: 1.136, 95% CI: 0.872 to 1.478) players received more cards when exposed to 25-50% of the total playing time. The match location was not associated with the occurrence of cards. Conclusions The association of playing position and situational variables with the occurrence of cards is moderated by the players' starting status (starter and non-starter) in the Brazilian first-division soccer championship.